Animal evolution during domestication: the domesticated fox as a model - Trut, Lyudmila (2009)
We review the evolution of domestic animals, emphasizing the effect of the earliest steps of domestication on its course. Using the first domesticated species, the dog (Canis familiaris) as an illustration, we describe the evolutionary specificities of the historical domestication, such as the high level and wide range of diversity. We suggest that the process of earliest domestication via unconscious and later conscious selection of human-defined behavioral traits may accelerate phenotypic variations. The review is based on the results of the long-term experiment designed to reproduce early mammalian domestication in the silver fox (Vulpes vulpes) selected for tameability, or amenability to domestication. We describe changes in behavior, morphology and physiology that appeared in the fox during its selection for tameability and that were similar to those observed in the domestic dog. Based on the experimental fox data and survey of relevant data, we discuss the developmental, genetic and possible molecular-genetic mechanisms of these changes. We assign the causative role in evolutionary transformation of domestic animals to selection for behavior and to the neurospecific regulatory genes it affects.